2016
DOI: 10.1080/03019233.2016.1144547
|View full text |Cite
|
Sign up to set email alerts
|

Development and application of electric arc furnace combined blowing technology

Abstract: A number of electric arc furnace (EAF) plants in China use high proportions of hot metal in the charge because of availability of excess liquid iron at the steelworks and/or because of the high price of scrap relative to hot metal. Liquid steel costs are still higher than the basic oxygen furnace as the EAF is not as efficient when refining liquid iron. EAF combined blowing technology has been modelled and installed in industrial plants with the aim of increasing stirring and hence improving refining. The indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 2 publications
0
12
0
Order By: Relevance
“…It is not possible to compare because the combinations are different; however, the magnitude reported by Caffery et al [ 85 ] is quite high, about 14–15 cm s −1 using oxygen injection and bottom gas stirring. For a similar arrangement, Ma et al [ 46 ] reported an average velocity of 2.6 cm s −1 . These results suggest the need of further research to clarify the individual contribution of each stirring mechanism and a comparison with the high‐stirring intensities in the BOF.…”
Section: Bottom Gas Stirring In the Eafmentioning
confidence: 95%
See 2 more Smart Citations
“…It is not possible to compare because the combinations are different; however, the magnitude reported by Caffery et al [ 85 ] is quite high, about 14–15 cm s −1 using oxygen injection and bottom gas stirring. For a similar arrangement, Ma et al [ 46 ] reported an average velocity of 2.6 cm s −1 . These results suggest the need of further research to clarify the individual contribution of each stirring mechanism and a comparison with the high‐stirring intensities in the BOF.…”
Section: Bottom Gas Stirring In the Eafmentioning
confidence: 95%
“…In the direct system, the porous plug is in contact with liquid steel, stirring intensity is higher, gas consumption is lower, the plume is narrow and forms a slag eye, the stirring conditions are carefully controlled, and porous plugs have a short life span requiring more maintenance. Ma et al [ 46 ] reported a life span of 700 heats for a direct system. A disadvantage of the direct system is the shallow bath of the EAF.…”
Section: Bottom Gas Stirring In the Eafmentioning
confidence: 99%
See 1 more Smart Citation
“…EAF bottom-blowing process [5] is blowing inert gas (Ar, N2) from the bottom of EAF. By inert gas mixing of molten steel in the furnace, increasing the electric arc furnace in steel liquefied learn composition and temperature of molten pool even.…”
Section: Introductionmentioning
confidence: 99%
“…Dong [17] considered that bottom-blowing could play an important role in energy saving and consumption reduces through its application in a consteel EAF. Ma [5] considered that the industrial application of the combined blowing technology in a number of steel plants indicates that the combined blowing technology of EAF can effectively improve the pool stirring strength and reaction dynamics condition of the molten pool, and optimise production.…”
Section: Introductionmentioning
confidence: 99%